Long-Chain Polyunsaturated Fatty Acids and Painful Temporomandibular Disorder in the Hispanic Community Health Study/Study of Latinos - Anne E. Sanders; Jianwen Cai; Martha L. Daviglus; Olga Garcia-Bedoya; Gary D. Slade (Public Health Nutrition)
ABSTRACT